Access to Information and Flood Early Warning System Management in Vang Vieng District, Vientiane Province - Keoduangded, Suvannakone; Kimmany, Bounhome; Phoumphone, Keopheth (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Nam Song is one of the tributaries of Nam Lik River, which is considered an important river that creates natural tourism value for the people in Vang Vieng District. Nam Song Dam is another dam built with the purpose of generating electricity and sending water to Nam Ngum 1 reservoir to increase the capacity of generating electricity. Due to the heavy rainfall in the upper part of the catchment area, the amount of water in the main river and tributaries has increased beyond the capacity of the natural stream, causing floods almost every year and increasing in intensity. Therefore, 2016 a modern flood warning system was developed and installed in Vang Vieng District, Vientiane Province to monitor and notify the people in the area. But the flood early warning system has not yet been evaluated for its effectiveness in management, including access to flood warning information for the people in the community. The main purpose of this research is to study the community's opinion on receiving information from a flood warning system in advance and to evaluate the community's participation in the management of the flood warning system. This research used the public interview form and actual observation within the research area to collect the necessary data and statistical analysis of the data obtained from the target group interview using SPSS. Based on the hypothesis that people access flood warning information in advance from official communication channels at least 80%, through the study, it can be concluded that sample households access flood warning information in advance through official channels 3 sources are not up to 80% namely: through the television, radio, and warning sound from flood warning poles, which is the only channel that sample households have access to more than 80% namely: access to information through the village television. For information through informal channels, such as word of mouth, 88% of them access the most, Facebook/telephone about 75%. From the results of the study, the provision of early warning information through the village telephone is the best and most suitable method in the study area. For word-of-mouth information that is more accessible to households, and it should be promoted. In that, access to warning information can make people be prepared; able to protect their lives and property. For participation in management; maintenance and monitoring of flood warning points is about 54%. Most of the people have already participated in the management according to the assignment of the organization and leading the relevant parties.